Challenges of internally displaced entrepreneurs in small machine-building enterprises in Dnipro - Novoselskyi, Yaroslav (Запоріжжя: ТДАТУ, 2026)
Dnipro, one of Ukraine’s major industrial centres, has become a destination for entrepreneurs displaced by the Russian invasion and occupation of Melitopol. In April 2024, a small enterprise specialising in the production and repair of turbines relocated from Melitopol to Dnipro. Forced to abandon its facilities and networks, the enterprise had to rebuild operations from the ground up. This case illustrates both the resilience of Ukraine’s industrial sector and the formidable challenges faced by internally displaced persons (IDPs) in restarting businesses under conditions of war.
Keywords: machine-building enterprises; turbine enterprise